THE THE ROLE OF AIRPORT SERVICE QUALITY: PERSPECTIVE FROM DEVELOPMENT OF THE TOURISM SECTOR - Shahparan, Mohammad; Salnikova, Elena; Klykov , Artem (Politeknik Pariwisata NHI Bandung, 2024)
The airport serves as a vital gateway in the international tourism industry, acting as the first and last impression for tourists visiting a destination. High airport service quality plays an essential role in enhancing the overall tourism experience and significantly influences passenger perceptions and satisfaction levels. Service quality at airports not only affects passengers' immediate experiences but also shapes their future intentions to revisit or recommend the destination to others. This paper examines the multifaceted role of airport service quality within the tourism sector, underscoring key elements such as convenience, comfort, cleanliness, accessibility of information, and overall efficiency of services offered. In addition, the paper delves into the ways that improved airport infrastructure, effective information dissemination, and enhanced security measures can contribute to creating a positive travel experience and promoting tourism development. A qualitative research methodology is employed, with data collected from various online sources focusing on airport service quality and its impact on tourism growth. By improving these service factors, airports can play a proactive role in fostering tourism sector expansion, encouraging positive word-of-mouth, and ultimately positioning themselves as attractive entry points that elevate the reputation and desirability of a destination.